2018
DOI: 10.1016/j.scitotenv.2017.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Household air pollution and chronic hypoxia in the placenta of pregnant Nigerian women: A randomized controlled ethanol Cookstove intervention

Abstract: In-utero exposure to HAP is associated with pathologic changes and HIF expression consistent with chronic hypoxia in placenta of firewood/kerosene-users compared to ethanol-users with less HAP exposure and Chicago women with no presumed HAP exposure. Presence of chronic hypoxic signature in placenta of women exposed to HAP has implications for adverse pregnancy complications and future growth and development of the young children. Future larger studies need to focus on HAP exposure and placental disorders like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Air pollution has already been linked to placental transcriptome changes (74), placental DNA methylation (75) and a reduced placenta weight (76). Further, women exposed to high levels of air pollution from cooking with solid fuels have shown chronic placental hypoxia (77) and fetal thrombotic vasculopathy (78). Adding to this body of knowledge, our data suggest that exposure to PM2.5 in vitro has the potential to induce cellular toxicity as well as hormone dysregulation, oxidative damage, inflammatory response, and interference with mitochondria in first trimester placental cells (HTR-8 cells).…”
Section: Discussionmentioning
confidence: 66%
“…Air pollution has already been linked to placental transcriptome changes (74), placental DNA methylation (75) and a reduced placenta weight (76). Further, women exposed to high levels of air pollution from cooking with solid fuels have shown chronic placental hypoxia (77) and fetal thrombotic vasculopathy (78). Adding to this body of knowledge, our data suggest that exposure to PM2.5 in vitro has the potential to induce cellular toxicity as well as hormone dysregulation, oxidative damage, inflammatory response, and interference with mitochondria in first trimester placental cells (HTR-8 cells).…”
Section: Discussionmentioning
confidence: 66%
“…IL-6, IL-1b) into the human circulation following exposure to PM has been demonstrated [17]. Changes in placental functions including altered gene expression and increases in markers of oxidative stress [28, 29], mitochondrial dysfunction and altered methylation profiles [3032], and endothelial and villi pathology [21] have been reported following inhalation of PM during human pregnancy. More recently, Qin and colleagues found that exposure to high levels of urban PM2.5 (particles ≤ 2.5 μm) induced cell-cycle arrest, inhibited migration and invasion of extravillous trophoblast cells [33].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to pollutant cooking fuel is associated with LBW [15]. Exposure to household air pollution (HAP) is associated with placental function (placental inflammation, placental hypoxia and thrombotic placental lesions) [44,45]. Exposure to these fuels affects placental function.…”
Section: Social and Demographic Factors (Table 2)mentioning
confidence: 99%